Analisis Unsur Mens Rea dalam Pertanggungjawaban Pidana Kasus Korupsi Tom Lembong - Shinta Aulia Zahrani; Gelar Ali Ahmad (IAIN Langsa, 2026)
This study aims to examine the doctrinal construction of mens rea in criminal liability, assess the fulfillment of the mens rea requirement in the corruption case involving Tom Lembong, and analyze its implications for legal certainty in the enforcement of anti-corruption law in Indonesia. This research employs a qualitative library research design using a normative juridical approach through statutory, case, and conceptual approaches. Primary and secondary legal materials were analyzed using descriptive-analytical methods supported by legal interpretation and content analysis. The findings demonstrate that establishing mens rea cannot rely solely on evidence of state financial loss or procedural irregularities but must be supported by proof of intent, knowledge, and conscious abuse of authority aimed at achieving an unlawful objective. The study further reveals that positioning mens rea as the central element of criminal liability strengthens legal certainty by distinguishing legitimate governmental discretion exercised in good faith from criminal abuse of authority. This framework also provides a more balanced standard for anti-corruption enforcement while reducing the risk of criminalization of public policy and reinforcing the principle of culpability within Indonesia’s criminal justice system.